Better Phonological Short-Term Memory Is Linked to Improved Cortical Memory Representations for Word Forms and Better Word Learning - Ylinen, Sari; Nora, Anni; Service, Elisabet (Frontiers in Human Neuroscience, 2020)
Language learning relies on both short-term and long-term memory. Phonological short-term memory (pSTM) is thought to play an important role in the learning of novel word forms. However, language learners may differ in their ability to maintain word representations in pSTM during interfering auditory input. We used magnetoencephalography (MEG) to investigate how pSTM capacity in better and poorer pSTM groups is linked to language learning and the maintenance of pseudowords in pSTM. In particular, MEG was recorded while participants maintained pseudowords in pSTM by covert speech rehearsal, and while these brain representations were probed by presenting auditory pseudowords with first or third syllables matching or mismatching the rehearsed item. A control condition included identical stimuli but no rehearsal. Differences in response strength between matching and mismatching syllables were interpreted as the phonological mapping negativity (PMN). While PMN for the first syllable was found in both groups, it was observed for the third syllable only in the group with better pSTM. This suggests that individuals with better pSTM maintained representations of trisyllabic pseudowords more accurately during interference than individuals with poorer pSTM. Importantly, the group with better pSTM learned words faster in a paired-associate word learning task, linking the PMN findings to language learning.